Towards Nuanced Understandings of the Identities of EAL Doctoral Student Writers - Macdonald, Shem; Schneider, Britta (Journal of Academic Writing, 2020)
The construct of identity in the space of English as an Additional Language (EAL) Higher Degree by Research (HDR) writing has been widely researched with studies exploring students’ identities as constructed through and in the process of writing. However, these studies are often presented in ways that focus on the challenges the writers face, citing language barriers and cultural differences and ascribing these students “closed subject positions” with “limited ways of talking about themselves” (Koehne, 2005, p. 118). In response to such deficit views, various studies have explored the multiple and varied identities of HDR EAL students as evident in their written reflections and other work, offering a wider range of views. We argue that there is a need for additional nuanced views of these student identities and how they are formed. In this paper we demonstrate how these can be gained by examining student identities as they emerge through spoken interaction. Applying a sociocultural linguistic framework that understands identities as emerging, situationally and relationally dependent (Bucholtz & Hall, 2005), we report how two students formed identities for themselves by talking to us about their experiences of writing using EAL. Our analysis provides nuanced understandings of the multiple identities of EAL HDR students that move beyond the deficit ones we were, and still are, frequently hearing in institutional discourses and demonstrates how the application of this framework can help articulate richness, variety and resourcefulness, and challenge essentialised identities of EAL doctoral student writers.